FAUNA OF OUR OCEANS – LITTORAL LIFE - Sharma, G.P. (SCHOOL SCIENCE, 2013)
The word ’ocean’ is derived from the name ’oceanus’ which the Greeks had given to a river that flowed, according to them, around the earth considered by them to be flat. However, as our knowledge about the earth and the oceans surrounding it increased, the wheel maps of the olden days were replaced by the most modern ones which now tell us that there are three great oceans in this world, viz., the Atlantic, the Pacific and the Indian. The last one is named as such because it washes our shores which extend over nearly 4700 kilometres. Regarding the origin of these oceans, it may be stated that in the beginning, even the earth was just a part of the sun. It was, therefore, as hot as the sun itself when it separated from it. Gradually, however, it cooled down with the result that its outer surface became rocky, but the inner portion still remained at a very high temperature on account of the hot gases which originally constituted it. These occasionally caused the eruptions of some of the rocks at their tips with the result that huge craters were formed and the hot lava flowed down the rocks. As a consequence of the high temperatures prevailing on the surface of the earth, it remained surrounded by clouds formed due to the condensation of the atmospheric vapour. Gradually, however, these clouds rained and the water, this collected in the huge craters and the valleys in between the rocks, formed the oceans.